Pleiotropic effect of vitamin D and supplementation - Kasprzak, Małgorzata; Kułaga, Monika; Kasprzak, Anna; Szostak, Barbara; Wielgosz-Biała, Sylwia; Grzybek, Monika; Mazur-Lesińska, Diana; Wilczyńska, Barbara; Tyszkiewicz, Krzysztof; Łozowski, Borys (Journal of Education, Health and Sport, 2025)
Calcitriol is the active form of vitamin D. It belongs to the family of hormones that are transcription factors for target protein genes. It is involved in many signalling pathways in cells, which is associated with its various essential functions in the body. It is synthesised in skin exposed to sunlight. It can be delivered to the body as food or supplemented, too. In the skin, exposed to ultraviolet rays (UVB), cholecalciferol is produced. Cholecalciferol can be supplemented to prevent vitamin D deficiency or to treat diseases. Cholecalciferol supplementation may not be effective in people with severe kidney diseases. The aim of this paper is to review broad effects of vitamin D and recent knowledge about the supplementation.